2000
DOI: 10.1021/op000023y
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the Impact of Ritonavir Polymorphs on the Late Stages of Bulk Drug Process Development

Abstract: Ritonavir (Kempf, D. J.; Marsh, K. C., Denissen, J. F.; McDonald, E.; Vasavanonda, S.; Flentge, C. A.; Green, B. E.; Fino, L.; Park, C. H.; Kong, X. P.; Wideburg, N. E.; Saldivar, A.; Ruitz, L.; Kati, W. M.; Sham, H. L.; Robins, T.; Stewart, K. D.; Hsu, A.; Plattner, J. J.; Leonard, J. M.; Norbeck, D. W. Proc. Natl. Acad. Sci. U.S.A. 1995, 92, 2484) is Abbott's novel protease inhibitor, for human immunodeficiency virus (HIV), the causative organism of acquired immunodeficiency syndrome (AIDS). It is marketed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
508
1
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(538 citation statements)
references
References 3 publications
6
508
1
6
Order By: Relevance
“…A culminating event was the temporary removal from the market of the life-saving protease inhibitor Norvir in 1998, which occurred because of the appearance of a previously unknown polymorph of the active ingredient ritonavir. 10 The marketed dosage form of Norvir consisted of gel-caps filled with a solution containing ritonavir. The new crystalline form is more stable, and therefore less soluble, than the old form and crystallized out of solution inside the gel-caps, rendering the formulation unmanufacturable.…”
Section: Polymorphsmentioning
confidence: 99%
“…A culminating event was the temporary removal from the market of the life-saving protease inhibitor Norvir in 1998, which occurred because of the appearance of a previously unknown polymorph of the active ingredient ritonavir. 10 The marketed dosage form of Norvir consisted of gel-caps filled with a solution containing ritonavir. The new crystalline form is more stable, and therefore less soluble, than the old form and crystallized out of solution inside the gel-caps, rendering the formulation unmanufacturable.…”
Section: Polymorphsmentioning
confidence: 99%
“…A well-known example of this problematic quality-activity relationship of a final dosage form is the case of Norvir 1 brand of ritonavir semisolid capsules. [1][2][3][4] Commercial start-up of the drug as a semisolid capsule formulation began in the early 1996, but 2 years later most of the final product lots started to fail in the dissolution tests. It was found that during storage, the drug converted to a new, until then unknown, thermodynamically more stable but less soluble polymorph of ritonavir, leading to a loss of bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that during storage, the drug converted to a new, until then unknown, thermodynamically more stable but less soluble polymorph of ritonavir, leading to a loss of bioactivity. [1][2][3][4] Another example of loss of activity has been reported for phenytoin (a drug used to control epilepsy), due to storage of the capsules in damp and cool conditions. 5 This has generated a demand to develop fast and flexible methods of measurement of polymorphic and pseudopolymorphic transformations inline during pharmaceutical processing and storage procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The late emergence of a thermodynamically more stable form (Form II) which unexpectedly precipitated from the semisolid capsule formulation led to the removal of the product from the market. The new crystal form (form II) appeared after conversion of metastable crystalline form I (Chemburkar et al, 2000;Bauer et al, 2001;Desikan et al, 2005;Miller et al, 2005). Ritonavir polymorphism was investigated using solid state spectroscopy and microscopy techniques including solid state NMR, near infrared spectroscopy, powder Xray diffraction and single crystal X-ray analysis.…”
Section: Ritonavirmentioning
confidence: 99%